Of legal history, jurisprudence and insanity – “Wrong or contrary to law" in section 84 of the Penal Code re-considered - PHANG, Andrew B.L. (Institutional Knowledge at Singapore Management University, 1995)
This article considers, from the perspectives of legal history and jurisprudence, longstanding controversy surrounding the interpretation of the phrase "wrong or contra to law" in section 84 of the Penal Code, and suggests that the evidence points to interpretation that "wrong" means "legally wrong" or "contrary to law". It also consid the practical implications that follow from such an interpretation, which implicatio would allow for some role, nevertheless, for extral